2015
DOI: 10.1515/tjj-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Characteristics of Squeeze Film Damper during Maneuver Flight

Abstract: The rotor systems of an aero engine will endure additional centrifugal force and gyroscopic moment during maneuver flight. A maneuver fly mechanical simu lator is designed and experimental investigations on dy namics of squeeze film damper (SFD) under the different additional centrifugal force and gyroscopic moment are carried out. The results show that the maneuver flight weaken effectiveness of the SFD, the additional centrif ugal force and gyroscopic moment caused by maneuver flight will change film damping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Chen et al (2020) was analyzed the effect of SFD on the nonlinear characteristics of the rotor system supported by different supports. Wang et al (2015) and Zhou et al (2013) studied designed and experimental investigations on dynamics of SFD and verified the authenticity of the simulation results with experiments. Childs (2013) studied that depending on the size of the damper, the damper is ineffective and likely to result in large amplitude motion with possible subsynchronous frequencies.…”
Section: Introductionmentioning
confidence: 67%
“…Chen et al (2020) was analyzed the effect of SFD on the nonlinear characteristics of the rotor system supported by different supports. Wang et al (2015) and Zhou et al (2013) studied designed and experimental investigations on dynamics of SFD and verified the authenticity of the simulation results with experiments. Childs (2013) studied that depending on the size of the damper, the damper is ineffective and likely to result in large amplitude motion with possible subsynchronous frequencies.…”
Section: Introductionmentioning
confidence: 67%
“…Xu and Liao [6] studied the vibration response characteristics of a Jeffcott rotor with squeeze film dampers (SFDs) in maneuvering flight environment, and the numerical analysis indicated that the SFDs effectively suppress the transient vibrations caused by maneuvering flight. Based on this, Wang et al [7] designed a rotor test rig that applies timevarying centrifugal force and gyroscopic moment on the rotor system according to maneuvering flight. e influence of the oil film clearance, the unbalanced force, and maneuvering flight parameters on the vibration reduction performance of SFDs was then analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Using the static eccentric condition and vibration reduction mechanism, the parameter range of SFD was designed and the sensitivity of the system to the double frequency excitation ratio was verified [22][23][24]. The design and experimental investigation of the dynamics of SFD was studied, and the reliability of the simulation results was verified through experiments [25,26]. The effect of SFD on the nonlinear characteristics of the rotor system supported by different supports was analyzed [27][28][29].…”
Section: Introductionmentioning
confidence: 99%